The Role of Argumentation and Institutions for Labour Migration in the European Union – Exemplified by Spanish labour migration to Germany. (13th October 2017) - Heimann, Christiane; Wieczorek, Oliver
Abstract: This contribution will show how institutions in Spain and Germany facilitated intra‐European labour mobility as a solution to a mismatch in the labour market. To this end, we have chosen the recruitment of Spanish job candidates for German employers as an example. Employing Bourdieu's field‐theoretical framework as well as expert interviews, we highlight the role of institutional agents encouraging labour migration. We analysed 30 expert interviews to gain insights from institutional agents that facilitate labour migration in the Spanish and the German labour market. Our findings show how these agents use their resources to legitimize policies and create sustainable structures steering labour migration and integration.